Biological Characterization of Yellow Fever Viruses Isolated From Non-human Primates in Brazil With Distinct Genomic Landscapes - Furtado, Nathália Dias; Raphael, Lidiane de Menezes; Ribeiro, Ieda Pereira; de Mello, Iasmim Silva; Fernandes, Déberli Ruiz; Gómez, Mariela Martínez; dos Santos, Alexandre Araújo Cunha; Nogueira, Mônica da Silva; de Castro, Márcia Gonçalves; de Abreu, Filipe Vieira Santos; Martins, Lívia Carício; Vasconcelos, Pedro Fernando da Costa; et al. (Frontiers in Microbiology, 2022)
Since the beginning of the XXI Century, the yellow fever virus (YFV) has been cyclically spreading from the Amazon basin to Brazil's South and Southeast regions, culminating in an unprecedented outbreak that started in 2016. In this work, we studied four YFV isolated from non-human primates obtained during outbreaks in the states of Rio Grande do Sul in 2008 (PR4408), Goiás (GO05), and Espírito Santo (ES-504) in 2017, and Rio de Janeiro (RJ 155) in 2019. These isolates have genomic differences mainly distributed in non-structural proteins. We compared the isolates' rates of infection in mammal and mosquito cells and neurovirulence in adult mice. RJ 155 and PR4408 YFV isolates exhibited higher infectivity in mammalian cells and neurovirulence in mice. In mosquito Aag2 cells, GO05 and PR4408 displayed the lowest proliferation rates. These results suggest that RJ 155 and PR4408 YFV isolates carry some genomic markers that increase infectivity in mammal hosts. From this characterization, it is possible to contribute to discovering new molecular markers for the virulence of YFV.